ECONOMIC ASPECTS OF FIXED-CAPITAL OBSOLESCENCE. - Moyer, C. A. (The Accounting Review, 1939)
Abstract In this article, the author discusses economic aspects of fixed-capital obsolescence illustrating issues in patent laws and ordering. He describes that prior to the twentieth century, obsolescence of fixed capital or intellectual assets was usually treated as a factor of depreciation. In recent years an attempt has been made in some instances definitely to separate depredation and obsolescence. ice. Although alike in their fundamental nature, the two are traditionally separated because the latter is consumed in a single use, while the consumption of the former extends over a longer period of time. The physical results of depreciation are apparent, but the same cannot be said of financial results. Accountants also suggested that in many cases producers must use their judgment as to what they consider the best time to retire certain assets from use. There has been considerable agitation in recent years toward a change in the patent laws. It is claimed that modern economic conditions require several modifications of present laws in order to prevent the misuse of patent rights.